Sulfate Resistance of Blended Cements (Limestone Illite Calcined Clay) Exposed Without Previous Curing - Rossetti, Agustín (2020)
Durability in aggressive environments is an important factor to extend the service life of concrete and the use ternary blended cements (limestone filler + calcined clays) can contribute to this purpose. In sulfate environments, the effects of supplementary cementing materials depend on the concentration, Portland cement and the progress of hydration reactions. Low level of limestone filler replacement influences the stabilization of AFt due to formation of monocarboaluminate, but high replacement increases the effective w/c and the capillary porosity promoting sulfate penetration. The use of active pozzolans suppresses the sulfate attack by minimizing both ettringite and gypsum formation. It is generally assumed that curing prior to sulfate exposure should be extended to allow the development of the pozzolanic reaction and subsequent reduction of portlandite content, pore size structure refinement and permeability reduction. However, in most field applications, concretes exposed to sulfate attack are cast in situ and thus, these are exposed to sulfate since early ages. This paper evaluates the sulfate resistance of an illitic-calcined clay and limestone filler when the cement is exposed immediately to aggressive environments. In this paper, the external sulfate resistance of blended cements containing 30% replacement of limestone filler and/or calcined clay (C30F, C30CC and C15F15CC) are analysed. Two different calcined clays from Buenos Aires, Argentina were selected. Mortar prisms and cement paste cubes were fabricated and exposed to a sodium sulfate solution after 2 days. Comparison of sulfate resistance was based on the expansion, mass variation, visual appearance and compressive strength . Furthermore, the evolution of microstructure of blended cements exposed to sodium sulfate solution was characterized by XRD tests on the external surface and the core of cement-blended pastes.